SCANNING TECHNIQUE IN DEVELOPING STUDENTS READING COMPREHENSION - Thamrin, Nur Sehang (Kreatif, 2012)
Abstract: One of the objectives of teaching English for university students is the students are expected to understand the reading text. However, it is very difficult for the students to catch the message from the reading text as they have limited words and reading strategies. This research was intended to solve the students’ problem relating to the reading comprehension. The aim of this research is to prove whether the implementation of scanning technique is effective to develop students’ reading comprehension. Pre-experimental research design is implemented as the resercher only used one class experimental. In choosing the sample of the research, purposive sampling technique is applied. In collecting the data the researcher administered test; pre-test and post-test. Pre-test is used to find out the students’ real competence in doing the reading test, while post-test is used to determine the effect of scanning technique in developing the students’ reading comprehension. After analysing the data statisticaly, the result shows that there is a significant improvement toward the students’ competence in reading comprehension. The score of the students’ test increases from 4.48 of pre-test to 9.1 of post test. It means that the implementation of scanning technique contributes significantly toward the students’ reading comprehension. Keywords: scanning, technique, comprehension